Experimental characterization of disordered and ordered aggregates populated during the process of amyloid fibril formation. - Carulla, N; Zhou, M; Arimon, M; Gairí, M; Giralt, E; Robinson, C; Dobson, C (2009)
Recent experimental evidence points to intermediates populated during the process of amyloid fibril formation as the toxic moieties primarily responsible for the development of increasingly common disorders such as Alzheimer's disease and type II diabetes. We describe here the application of a pulse-labeling hydrogen-deuterium (HD) exchange strategy monitored by mass spectrometry (MS) and NMR spectroscopy (NMR) to characterize the aggregation process of an SH3 domain under 2 different conditions, both of which ultimately lead to well-defined amyloid fibrils. Under one condition, the intermediates appear to be largely amorphous in nature, whereas under the other condition protofibrillar species are clearly evident. Under the conditions favoring amorphous-like intermediates, only species having no protection against HD exchange can be detected in addition to the mature fibrils that show a high degree of protection. By contrast, under the conditions favoring protofibrillar-like intermediates, MS reveals that multiple species are present with different degrees of HD exchange protection, indicating that aggregation occurs initially through relatively disordered species that subsequently evolve to form ordered aggregates that eventually lead to amyloid fibrils. Further analysis using NMR provides residue-specific information on the structural reorganizations that take place during aggregation, as well as on the time scales by which they occur.